Reduced complexity MLSD receivers for nonlinear optical channels - Maggio, Gabriel Nicolás (2014)
We present a novel maximum likelihood sequence detection (MLSD) receiver structure for nonlinear channels. This scheme is derived by treating the NLC as a multiple input/multiple output system. Then, orthogonal signal components are computed using a special form of space-time whitened matched filter (ST-WMF) obtained by a modified Gram-Schmidt orthogonalization of the Volterra kernels of the NLC. The MLSD receiver consists of the ST-WMF followed by a Viterbi detector (VD) with multidimensional branch metrics. The space orthogonalization and noise whitening achieved by the ST-WMF provide an efficient way to reduce the receiver complexity in the presence of highly dispersive NLC. Complexity reduction is crucial in practical applications such as intensity modulation/direct detection (IM/DD) optical channels. As an example, the number of states of the VD in ST-WMF-MLSD required on a 10 Gb/s, 700 km, IM/DD fiber-optic link is reduced eight times compared with an oversampled MLSD.